In vitro plant regeneration of Coccinea cordifolia (Linn.) Cogn., an anti-diabetic medicinal plant (Bangladesh Journal of Scientific and Industrial Research, 2012)
An efficient protocol was developed for in vitro plant regeneration of a popularly used anti-diabetic medicinal plant, Coccinea cordifolia (Linn.) Cogn.(Cucurbitaceae) through direct organogenesis using shoot tip and nodal explants. Best shoot induction was observed on MS basal medium supplemented with 0.5 mg/l BAP, in which 88.2% of nodal explants responded to produce maximum number (6.2 ± 0.58) of shoots per culture. In vitro raised shoots rooted on half strength MS medium with 0.5 mg/l IBA. The survival rate of regenerated plantlets was 85%.   DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11450   Bangladesh J. Sci. Ind. Res. 47(2), 187-190, 2012